2021
DOI: 10.1016/j.breast.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Decisional conflict in breast cancer patients considering immediate breast reconstruction

Abstract: Background: Breast cancer (BC) patients who are treated with mastectomy are frequently offered immediate breast reconstruction. This study aimed to assess decisional conflict in patients considering immediate breast reconstruction, and to identify factors associated with clinically significant decisional conflict (CSDC). Methods: Baseline data of a multicenter randomized controlled trial evaluating the impact of an online decision aid for BC patients considering immediate breast reconstruction after mastectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Interestingly, the study found that after adjusting for various factors, disease knowledge did not show a signi cant correlation with decision con ict. This nding is consistent with a study on the con ict of decision-making in breast reconstruction among breast cancer patients 29 , suggesting that making a treatment decision for IBD may create uncertainty for the patient regardless of their prior knowledge. Decisional con ict may be more closely related to the perceived knowledge of patients rather than their actual knowledge.…”
Section: Decisional Con Ictsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the study found that after adjusting for various factors, disease knowledge did not show a signi cant correlation with decision con ict. This nding is consistent with a study on the con ict of decision-making in breast reconstruction among breast cancer patients 29 , suggesting that making a treatment decision for IBD may create uncertainty for the patient regardless of their prior knowledge. Decisional con ict may be more closely related to the perceived knowledge of patients rather than their actual knowledge.…”
Section: Decisional Con Ictsupporting
confidence: 90%
“…Previous research has shown that decisional con ict can be exacerbated by anxiety and depression, and vice versa 29,33 . When patients are uncertain and regret existing decisions, anxiety, and depression may be exacerbated.…”
Section: Decisional Con Ictmentioning
confidence: 99%
“…PtDAs have shown to be significantly beneficial to patients in various medical topics, such as choice of medication for type 2 diabetes mellitus [12], surgical intervention for breast cancer [19], paediatric vaccination of rotavirus [20], and clinical care of lumbar degenerative diseases [21]. The use of PtDAs in shared clinical decision-making encourages patients and decision-makers to ask questions, thereby making them better informed to make proper medical decisions for themselves or their family.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase in the incidence with a rate of up to 3.5% over the preceding decade [ 13 ]. Surgery remains the foundation of treatment for breast cancer worldwide, and current current trends in surgical care including breast conservation surgery, mastectomy and reconstruction [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ]. There has been a paradigm shift in the management of breast cancer and the advent of oncoplastic breast surgery has revolutionised the concept of breast preservation, utilising limited tissue resection as opposed to a mastectomy [ 20 ], [ 21 ], [ 22 ], [ 23 ], [ 24 ], [ 25 ], [ 26 ], [ 27 ].…”
Section: Breast Reconstruction Prior To Covid-19mentioning
confidence: 99%
“…At most breast centres, the majority of reconstructions is performed immediately, in a joint procedure between the breast surgeon, who performs the mastectomy, and the plastic surgeon [ 15 ], [ 19 ], [ 31 ], [ 34 ], [ 35 ], [ 36 ], [ 37 ]. Pre-operatively, this allows for mastectomy skin sparing incisions to be discussed between the two teams which can then be incorporated in the final decision on the optimal reconstruction to best suit the patient.…”
Section: Breast Reconstruction Prior To Covid-19mentioning
confidence: 99%